Volatility level dependence and the CEV market model - Yeung, Alan (Graduate School of Business (GSB), 2021)
Interest-rate volatility is known to be level-dependent. However, Filipovic, Larsson and Trolle (2017) found that volatility becomes more level-dependent as the interest rate approaches the zero lower bound. This varying volatility level-dependence feature motivates the use of CEV market model to model the interest rate. In this dissertation, we compare the lognormal forward LIBOR market model, the CEV market model and the normal market model through regression analysis, hedging analysis and calibration analysis to assess their performance. The investigation is performed using EURIBOR 10-year interest-rate caps with various strike rates. This research work has a significant impact as the industry often needs to hedge interestrate caps. We show that although the CEV market model best calibrates to market prices, the normal market model is the best in terms of hedging interest-rate caps.